A case report of huge perirenal liposarcoma associated with renal cell carcinoma and reviews of three previous cases - Liu, Zhe (Int J Clin Exp Med, 2014)
Retroperitoneal liposarcoma (RPLS) is a rare malignant tumor yet with a high recurrence rate. It is mostly observed in limbs and during retroperitoneal clearance, and accounts for nearly 40% of all adult retroperitoneal soft tissue sarcomas [1]. Renal cell carcinoma (RCC) is a common cancer developed in urinary system and its occurrence rate accounts for 3% of whole body malignant tumors [2]. In this report, we present a case of large perirenal liposarcoma associated with RCC, which is to date the fourth identified case. We analyzed the clinical pathologic data of this patient and reviewed the other three cases. Compared to the other cases, this patient is diagnosed at the youngest age and the liposarcoma tumor is with the largest diameter. Moreover, we have been following up the patient after operation for the longest time. All of these made this report rare and important.